Problems of collisions between adjacent steel structures under earthquake excitation = Problemy zderzeń pomiędzy sąsiadującymi konstrukcjami stalowymi poddanymi obciążeniom sejsmicznym - Sołtysik, Barbara; Jankowski, Robert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Nowadays, the high level of urbanization forces the engineers to design closely-separated structures and to take into account many factors influencing their response, including collisions between them due to insufficient separation distance during moderate to strong ground motions.
Keywords: obciążenia sejsmiczne; konstrukcje stalowe; analiza numeryczna; earthquake excitation; structural pounding; steel structures; experimental study; numerical analysis